Variable Melt Production Rate of the Kerguelen HotSpot Due To Long‐Term Plume‐Ridge Interaction. Issue 1 (8th January 2018) - Bredow, Eva; Steinberger, Bernhard
Abstract: For at least 120 Myr, the Kerguelen plume has distributed enormous amounts of magmatic rocks over various igneous provinces between India, Australia, and Antarctica. Previous attempts to reconstruct the complex history of this plume have revealed several characteristics that are inconsistent with properties typically associated with plumes. To explore the geodynamic behavior of the Kerguelen hotspot, and in particular address these inconsistencies, we set up a regional viscous flow model with the mantle convection code ASPECT. Our model features complex time‐dependent boundary conditions in order to explicitly simulate the surrounding conditions of the Kerguelen plume. We show that a constant plume influx can result in a variable magma production rate if the plume interacts with nearby spreading ridges and that a dismembered plume, multiple plumes, or solitary waves in the plume conduit are not required to explain the fluctuating magma output and other unusual characteristics attributed to the Kerguelen hotspot. Key Points: Constant plume influx can result in variable melt production rate due to plume‐ridge interaction Ninetyeast Ridge has been created by on‐ridge volcanism, with plume material from below the Australian plate Amsterdam‐Saint Paul Plateau has been generated by plume material flowing toward the Southeast Indian Ridge